Barbed wire diplomacy Britain, Germany, and the politics of prisoners of war 1939-1945 - Wylie, Neville, 1966- (Oxford University Press, 2010)
This book examines how the UK government protected the lives, interests, and well-being of its POWs in Nazi Germany. The comparatively good treatment of British POWs in Germany has been explained in terms of self-interest. Wylie presents a more nuanced picture of Anglo-German relations and the politics of prisoners of war.